Strategi Dakwah dan Faktor Pengaruh - Najamuddin Najamuddin (TASAMUH: Jurnal Studi Islam, 2020)
Along with the development of today's world with all existing dynamics, every organization oriented to the development of Islamic da'wah is required to be able to formulate a strategy and its application. On the other hand it is also demanded to be able to improve itself in getting around the da'wah, so what message of syar'i can be accepted by mad'u (object of preaching). No exception for a profit organization (non-profit), and any da'wah organization that is purposeful existence and survival, then it must be able to determine every policy direction and to implement the right strategy to carry out its vision, mission, and to anticipate all possibilities, so what which became the ideals and goals of the organization can be achieved. Seeing the description of the phenomenology mentioned above, surely we realize that the role of strategy for the activities of da'wah is very important in determining an organization's policy steps. Then, related to the concepts, strategies, opportunities and challenges of the da'wah the writer will discuss in this article